Shaping the Future of the Global Food Systems Leadership Program: An Approach to Interdisciplinary Education - Easter, Adelaide (My University, 2025)
The Global Food Systems Leadership (GFSL) program at Kansas State University is a joint secondary major housed between the Staley School of Leadership and the College of Agriculture. The program helps equip students to address complex issues within the global food system. This honors project explores what would be needed to reform and develop the program to be offered as both an undergraduate major and a certificate. Through multiple methods, I interviewed those who founded the program, drew comparisons from peer and aspirational institutions, aligned the program with three of K-State's strategic plans, and analyzed feedback from student surveys. These methods allowed me to identify potential curriculum plans for both degree offerings, applied learning opportunities, target students for the program, and strategies for recruitment. Key findings from the survey demonstrate students' desire for program expansion through developing a standalone major and modifying the secondary major into a certificate option. This proposal then outlined the pathway for program approval at each step. Lastly, this project argues the importance and value of more interdisciplinary approaches to education and how the Global Food Systems Leadership program better prepares students to understand and lead in addressing the global food systems' most complex challenges, like food security, poverty, and climate change.